Pregnancy outcome in Thai patients with systemic lupus erythematosus - Sittiwangkul S. (2014)
The outcome of 48 pregnancies from 42 patients with systemic lupus erythematosus was studied. Their mean age and the duration of the disease were 28.47 and 4.42 years, respectively. The conception occurred when the disease was inactive or quiescent in 45 and active in 3. Four pregnancies were terminated by criminal abortion. Flares occurred in 16 pregnancies. The kidney and mucocutaneous system were the 2 organs that flared most commonly. The fetal outcomes were term delivery in 18 (40.90%), prematurity in 17 (38.64%), spontaneous abortion in 6 (13.64%) and still birth in 3 (6.82%). There was no statistical difference in pregnancy loss and successful delivery between pregnant patients with and without flares. Concerning 35 successful live births, those pregnancies without flares had significantly more full term deliveries (p < 0.02), higher gestational age (p < 0.002) and more birth weight (p < 0.001) than those with flares. Small for gestational age was seen in 20%. Pregnancy with active renal disease had a poor fetal outcome. There were no cases of congenital anomalies or neonatal lupus. Maternal complications were more common in patients with flares.